Growth and Blood Parameters of Weaned Crossbred Beef Calves Fed Forage Kale (Brassica oleracea spp. acephala) - Y. Chorfi; Y. Couture; G. F. Tremblay; R. Berthiaume; D. Cinq-Mars (Advances in Agriculture)
Forty lightweight calves (206.4±3.2 kg) were randomly distributed to four treatments: (Control) low nutritive value pasture and hay plus 1 kg d−1 of rolled barley; (Pasture) management intensive pasture; (Haylage) timothy haylage; and (Kale) 50% timothy haylage −50% kale pasture. Blood samples were analysed for thyroid hormones, liver enzymes, glucose, cholesterol, total proteins (TP), albumin, globulins, and urea-N. At the end of the trial, the Pasture group was the heaviest with 323.6±4.2 kg BW and 1.54 kg ADG. Final BW and ADG were similar for the Kale and Haylage groups. Blood T3 was higher for Kale than for the other groups. The T3/T4 ratio was greater for Control at the end of the experiment. There were no treatment differences for T4, aspartate aminotransferase (AST), gamma glutamyl transferase (GGT), glutamate dehydrogenase (GLDH), cholesterol, and glucose. Blood urea-N was lower for Kale and higher for Pasture; however albumin concentrations were greater for Pasture and similar for other treatments. Except for the Control group, calves had a lower concentration of circulating globulins at the end than at the beginning of the experiment. This study showed that Kale could be fed to backgrounding calves without detrimental effects on performance.